A survey of knowledge, attitude, and performance of Kerman residents on segregation and recycling of household solid wastes during COVID-19 period - Hoda Amiri; Majid Hashemi; Moghadameh Mirzaei; Abedin Iranpour (Environmental Health Engineering and Management, 2023)
Background: Awareness, knowledge, and attitude towards waste management, environmental factors of waste disposal sites and citizens’ as well as waste generators’ behaviors should be considered for implementing a waste segregation plan at the source. Methods: The statistical population of this cross-sectional study includes 150 000 households living in Kerman. The sample size is calculated as 444 individuals using a stratified sampling method considering a 15% withdrawal probability. The correlation between Kerman citizens’ demographic data (age, gender, mean income, and household head’s educational level) and behavioral patterns (knowledge and awareness, attitude and behavior) regarding waste management and environmental factors of waste disposal sites was evaluated using SPSS software. Results: Examining the variables indicates that attitude, environmental factors, behavior, awareness, and knowledge have the highest mean and standard deviation, respectively. The highest mean score of awareness and knowledge was observed among individuals who earned 40 million IRR and higher income (2.55 ± 0.24) and those who had a PhD degree (2.63 ± 0.27). The results show that one unit increase in the score of awareness and knowledge, attitude and environmental factors could increase the mean behavior score. Conclusion: Teaching the households waste-related environmental issues and how to properly separate recyclable waste as well as providing correct information regarding the current (COVID-19 period) and future plans and policies of the waste management organization, and developing suitable motivational mechanisms could improve the performance level of a society.